Differences in aerobic capacity of basketball players by gender, age, and relative age effect - Gottlieb, R.; Shalom, A.; Alcaraz, P. E.; Calleja-González, J. (Journal of Human Sport & Exercise, 2023)
When playing basketball, athletes must optimally perform repeated short sprints with minimal recovery time, requiring both anaerobic and aerobic abilities, including high VO2max. Yet differences have been seen between young male and female basketball players in this measure. The aim of this quantitative study was to examine differences in players` VO2max by gender, age group, and relative age effect (RAE) using the novel Yo-Yo Recovery Test for Basketball Players. The study included 438 young basketball players, male and female, from a range of Israeli leagues, who were divided into three categories: under-14, under-16, and under-18. To assess RAE, the participants in each category were divided into three trimesters of four months, based on their date of birth. The participants` VO2max was assessed using the novel aerobic test. In this study, we hypothesized that male players will exhibit greater aerobic capacity than female players of the same age and that older players will exhibit greater aerobic capacity than younger ones. Our findings supported these hypotheses, as male players presented better physical fitness results than female players in all age categories. Moreover, female players in the under-18 category presented better results than those in the under-14 category, but not more than those in the under-16. Differences in the relative age effect on performance were seen between the genders and within the female participants. While the male participants presented a steady improvement with age, the results of the girls showed a different pattern. The findings are presented in an achievement table that presents the expected physical fitness results by age and gender, for the benefit of basketball coaches and fitness trainers when assessing their players` aerobic capacity.